Dynamic volatility spillovers across shipping freight markets - Tsouknidis, Dimitris (My University, 2016)
. This paper examines the existence of dynamic volatility spillovers within and between the dry-bulk and tanker freight markets by employing the multivariate DCC-GARCH model and the volatility spillover index developed by Diebold and Yilmaz (2012, 2009). This methodology is invariant to ordering the variables when estimating a VAR model and allows for the disaggregation of volatility spillovers in total, directional, net and net pairwise. Results reveal the existence of large time-varying volatility spillovers across shipping freight markets, which are more intense during and after the global financial crisis.
Keywords: Dynamic volatility spillovers; Shipping freight markets; VAR models; freight transport; multivariate analysis; numerical model; spillover effect